2013
DOI: 10.1177/1474515113491649
|View full text |Cite
|
Sign up to set email alerts
|

‘I am still a bit unsure how much of a heart attack it really was!’ Patients presenting with non ST elevation myocardial infarction lack understanding about their illness and have less motivation for secondary prevention

Abstract: Patients with NSTEMI in this study expressed very different perceptions of their illness compared to those experiencing STEMI. Patients' clinical presentation and treatment experience during an AMI can impact on their illness perception, motivation for behavioural change and uptake of cardiac rehabilitation. Nurses should consider the patients' illness experience and perception when planning secondary prevention interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 23 publications
1
34
0
3
Order By: Relevance
“…Curry et al 351 did not highlight early initial assessment, but the importance we ascribe to this process is consistent with studies by investigators in Canada 485 and England. 486,487 Better information about AMI for patients is a key finding of several studies 483,[488][489][490] and a core feature of good-quality discharge. The importance of strong interdisciplinary communication and co-ordination has also been emphasised.…”
Section: Visible Cardiology Leadershipmentioning
confidence: 99%
“…Curry et al 351 did not highlight early initial assessment, but the importance we ascribe to this process is consistent with studies by investigators in Canada 485 and England. 486,487 Better information about AMI for patients is a key finding of several studies 483,[488][489][490] and a core feature of good-quality discharge. The importance of strong interdisciplinary communication and co-ordination has also been emphasised.…”
Section: Visible Cardiology Leadershipmentioning
confidence: 99%
“…Dullaghan et al. () found that the patients expressed an understanding of the condition as chronic and were therefore motivated to make lifestyle changes. Kähkönen et al.…”
Section: Introductionmentioning
confidence: 99%
“…Dullaghan et al . () found that STEMI patients (treated with PPCI or thrombolysis) viewed their illness as serious and life‐threatening and were committed to making lifestyle changes.…”
Section: Introductionmentioning
confidence: 99%